2002
DOI: 10.1122/1.1427908
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler velocimetry measurements of particle velocity fluctuations in a concentrated suspension

Abstract: Recent statistical constitutive models of suspensions of neutrally buoyant, non-Brownian, noncolloidal, solid spheres in Newtonian fluids suggest that the particles nijgrate in response to gradients in "suspension temperature," defined as the average kinetic energy contained in the particle velocity fluctuations. These models have not yet been compared systematically with experimental data.In addition, the "temperature" models assume isotropic particle velocity fluctuations, since the "suspension temperature" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
4
17
2
Order By: Relevance
“…Specifically, the component of the temperature in the direction of flow was found to decrease with concentration, that in the direction of the gradient stayed constant, while that in the vorticity direction initially increased in magnitude with increasing concentrations and then decreased for concentrations larger than 40%. Finally, and most surprisingly, Shapley et al (2002) found that, whereas the fluctuations in the direction of the flow increased linearly with shear rate (as expected for any flow in the Stokes regime), the STD in the vorticity direction increased non-linearly, while that in the gradient direction slightly decreased with shear rate.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Specifically, the component of the temperature in the direction of flow was found to decrease with concentration, that in the direction of the gradient stayed constant, while that in the vorticity direction initially increased in magnitude with increasing concentrations and then decreased for concentrations larger than 40%. Finally, and most surprisingly, Shapley et al (2002) found that, whereas the fluctuations in the direction of the flow increased linearly with shear rate (as expected for any flow in the Stokes regime), the STD in the vorticity direction increased non-linearly, while that in the gradient direction slightly decreased with shear rate.…”
Section: Introductionmentioning
confidence: 87%
“…Even an apparently very simple case, that of determining the dependence on the shear rate of the velocity fluctuations in simple shear flows, remains a matter of some controversy (Shapley et al 2002). What is clear is that, although the suspension might be homogeneous at macroscopic scales, the continuous rearrangements in the suspension microstructure and the corresponding hydrodynamic interactions between particles lead to fluctu-ations in the particle velocities about their mean values, in both the transverse and the flow directions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations